2019
DOI: 10.2478/popets-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Skip, Skip, Skip, Accept!!!: A Study on the Usability of Smartphone Manufacturer Provided Default Features and User Privacy

Abstract: Smartphone manufacturer provided default features (e.g., default location services, iCloud, Google Assistant, ad tracking) enhance the usability and extend the functionality of these devices. Prior studies have highlighted smartphone vulnerabilities and how users’ data can be harvested without their knowledge. However, little is known about manufacturer provided default features in this regard—their usability concerning configuring them during usage, and how users perceive them with regards to privacy. To brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On the other hand, although the AAID is supposed to be a non-persistent identifier since it can be reset through the system settings, there are two main reasons for also considering it, in practice, as potentially persistent. First, data subjects are prone to preserving default privacy settings [47], especially when such settings are hard to discover and understand (the option to reset the AAID is 6 steps deep) [48]. Second, a recent related work [40] found that 74.7% of recipients who receive AAIDs also receive other persistent identifiers, nullifying the nonpersistence property and also allowing a data subject to be tracked over time and across resets.…”
Section: Personal Data Cross-border Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although the AAID is supposed to be a non-persistent identifier since it can be reset through the system settings, there are two main reasons for also considering it, in practice, as potentially persistent. First, data subjects are prone to preserving default privacy settings [47], especially when such settings are hard to discover and understand (the option to reset the AAID is 6 steps deep) [48]. Second, a recent related work [40] found that 74.7% of recipients who receive AAIDs also receive other persistent identifiers, nullifying the nonpersistence property and also allowing a data subject to be tracked over time and across resets.…”
Section: Personal Data Cross-border Transfersmentioning
confidence: 99%
“…"It is our intention to transfer certain information to third parties in order to better help your experiences with our product. However, we shall at all times be in full compliance with provisions [45][46][47][48][49]…”
Section: Figure 9 Testing Timelinementioning
confidence: 99%
“…BA15 (complex interface and function) was discussed in 23% of the primary studies. In [LT41], an empirical study revealed that complex interface is complicated for elderly users because of their disabilities; therefore, the interface should be easy to use for elderly people and if possible help tooltips should be provided [33].…”
Section: Identified Barriers Using An Slrmentioning
confidence: 99%
“…First, research on the role of default settings indicates the ability of defaults to influence human behavior, both in the analog and digital world (Bradshaw & DeNardis, 2019;Shah & Kesan, 2008;Shah & Sandvig, 2008;Soh, 2019;Willis, 2013;Zuiderveen Borgesuis, 2015). Second, research shows that most users do not change the default settings (Dinner et al, 2011;Ramokapane et al, 2019;Shah & Sandvig, 2008;Sunstein, 2013;Svirsky, 2019;Watson et al, 2015). These points together suggest that there is incredible and intrinsic, though hidden, power in technology settings, including those set by social media companies.…”
Section: Critical Frameworkmentioning
confidence: 99%